2020
DOI: 10.1108/jeee-11-2019-0168
|View full text |Cite
|
Sign up to set email alerts
|

Regional entrepreneurial ecosystems in Chile: comparative lessons

Abstract: Purpose This paper aims to deal with different experts’ perceptions of entrepreneurial ecosystems (EEs) from central to non-central regions to evaluate if there was any evolution (or involution), comparing the results with those of a previous similar study on Chile from 2013, and it follows to replicate and improve our knowledge of the entrepreneurial opportunities. Design/methodology/approach One of the Global Entrepreneurship Monitor surveys, the National Experts’ Survey, was applied to a sample of N = 1,5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 85 publications
3
30
0
Order By: Relevance
“…Conceptually, we draw on previous embeddedness work (Granovetter 1973;Gulati 1998;Uzzi 1997) and integrate embeddedness into a three dimensional framework. This helps to better understand the underlying processes of entrepreneurial activity, especially in the context of regional EEs (de Villiers Scheepers et al 2018;Prencipe et al 2020;Villegas-Mateos 2020). Our research contributes to the theoretical foundations of EE research by specifying the relational dimensions between the individual level of family entrepreneurs and their environment into horizontal, vertical and spatial embeddedness.…”
Section: Introductionmentioning
confidence: 95%
“…Conceptually, we draw on previous embeddedness work (Granovetter 1973;Gulati 1998;Uzzi 1997) and integrate embeddedness into a three dimensional framework. This helps to better understand the underlying processes of entrepreneurial activity, especially in the context of regional EEs (de Villiers Scheepers et al 2018;Prencipe et al 2020;Villegas-Mateos 2020). Our research contributes to the theoretical foundations of EE research by specifying the relational dimensions between the individual level of family entrepreneurs and their environment into horizontal, vertical and spatial embeddedness.…”
Section: Introductionmentioning
confidence: 95%
“…Finally, and among the main learnings for the Manizales context, we point out, first, the strengthening of the relationships among the EE beneficiaries’ overtime to reinforce their engagement in the EE and second, guaranteeing the support to the EE actors, avoiding potential EE’s polarization around the salient agents. Although these recommendations can be applied to other similar EEs, ad hoc policies based on the understanding of each region’s specific nature, capabilities and risks (Villegas-Mateos, 2020) are required to maximize the potential of EEs.…”
Section: Discussionmentioning
confidence: 99%
“…It also has covered diverse areas, frameworks and models (Neck et al , 2004; Isenberg, 2011; Stam, 2015); components and dimensions (Fetters et al , 2010; Vogel and Fischler-Strasak, 2014; Kline et al , 2014; Mason and Brown, 2014). It has measured the performance or key factors for success or failure (Vogel, 2014; Kshetri, 2014; Pereverzeva, 2015; Ács et al , 2014) and, more recently, compared EEs in emerging economies (Villegas-Mateos, 2020). Within this literature, there are different definitions of EE.…”
Section: Entrepreneurial Families In Entrepreneurial Ecosystemsmentioning
confidence: 99%
“…Thinking of the most appropriate unit of analysis for this study, we embrace and emphasize that the emergence of entrepreneurial ecosystems comes not just from the recognition that places matters for entrepreneurs but also that entrepreneurs matter for the place (Bosma & Sternberg, 2014). Prior empirical studies confirmed that the location is important for examining EEs (Spigel, 2017;Villegas-Mateos, 2020). Therefore, in this study, we focus on the regional aspects of EE analysis from the city perspective rather than regional industrial clusters or national EEs (Autio et al, 2014).…”
Section: Introductionmentioning
confidence: 99%